(untitled) (Journal of Governance and Development (JGD), 2005)
Examining Malaysia’s administrative reforms program initiated by Dr. Mahathir Mohamad, Prime Minister of Malaysia, during 1981 to 2003 – the decade of modernization and faster economic growth – the authors analyze various programmes and reform policies introduced in the public administration system in Malaysia. Reforms that were carried out not only involved the federal government but also included the local government. This article identifies the administrative reform efforts that were introduced at the local government. Research was carried out from 2001 to 2002, to gauge the opinion of the senior officers who are currently serving in various units in the local governments in eight states, namely Perlis, Penang, Kedah, Kelantan, Sabah, Sarawak, Pahang and Terengganu. The eight states were chosen based on the assumptions that there is still some reform efforts implemented that have not met the targets yet. The result of the research shows that not all reform efforts introduced and adopted in those states are effective and successful. This means that the local government must be ready to carry out reforms and changes and to modernize their administrative system in order to compete with other local government in other advanced and developing countries.